Synthesizing depoliticization and responsibilization: The case of financial education in Israel. (October 2018) - Avigur-Eshel, Amit
Depoliticization and responsibilization are two frameworks that have contributed substantially to the analysis of state-society-economy relations under neoliberalism. They have also presented some limitations. The depoliticization literature has not looked into policymakers' active allocation of responsibility for economic outcomes to individuals. The Foucauldian responsibilization literature has largely overlooked who construct(s) the responsibilization governing technique and the political process through which this technique is produced. I argue that synthesizing the two frameworks can overcome these limitations and improve our ability to analyse the current state of the neoliberal project. I illustrate my argument by analysing the case of a governmental Financial Education Department in Israel. The department was established as a depoliticizing tool in a context of a popular protest that re-politicized economic policy. Its main concern was constructing financially responsible subjects. As political circumstances changed, political support waned and the department stagnated, although it never diminished.